Peran AI dalam Transformasi Komunikasi: Peluang dan Tantangan - Fahrudin, Atef; Nurhaipah, Titih; Sabda, Galang Ikhwan Aji (Universitas Majalengka, 2025)
The development of artificial intelligence (AI) has brought significant transformations in the field of communication. AI not only changes how information is delivered but also how human interactions occur, whether in interpersonal, organizational, or mass communication. This study aims to explore the role of AI in communication transformation by highlighting the challenges and innovations arising from the implementation of this technology. Through a literature review from various academic sources, this research identifies several key innovations, such as content automation, message personalization, and the use of chatbots in digital communication. However, ethical and technical challenges such as algorithmic bias, transparency, data privacy, and impacts on traditional jobs remain issues that need to be addressed. The study finds that while AI offers significant opportunities in enhancing communication efficiency and effectiveness, its sustainable implementation depends greatly on clear regulations, ethical awareness, and a balance between human and technological roles. This research provides insights for practitioners and academics to harness AI's potential while mitigating the risks arising during the communication transformation process.